2008
DOI: 10.4161/cc.7.20.6883
|View full text |Cite
|
Sign up to set email alerts
|

IRES-mediated translational control of AMAP1 expression during differentiation of monocyte U937 cells

Abstract: Global control of mRNA translation plays key roles in cell regulation, including growth, differentiation and apoptosis. Human monocyte-like U937 cells differentiate into macrophage-like cells upon 12-O-tetradecanoylphorbol-13-acetate (TPA) treatment, a process which is known to be accompanied with a large decrease in general protein synthesis. Here, we found that protein levels of AMAP1 (also called ASAP1 or DDEF1), a GTPase-activating protein for Arf GTPases, increase several fold during U937 cell differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
(98 reference statements)
0
8
0
1
Order By: Relevance
“…Protein levels of Arf6 and AMAP1 do not correlate with their mRNA levels [17,18,32]; and indeed their mRNAs both have long 5'-UTRs with large free-energy changes and are classified to be typical 'weak-mRNAs' that are known to be inefficiently translated on their own. We have moreover found that p53 mutations and micro-RNAs are also involved in the expression of Arf6 and AMAP1 mRNAs (will be published elsewhere).…”
Section: Discussionmentioning
confidence: 99%
“…Protein levels of Arf6 and AMAP1 do not correlate with their mRNA levels [17,18,32]; and indeed their mRNAs both have long 5'-UTRs with large free-energy changes and are classified to be typical 'weak-mRNAs' that are known to be inefficiently translated on their own. We have moreover found that p53 mutations and micro-RNAs are also involved in the expression of Arf6 and AMAP1 mRNAs (will be published elsewhere).…”
Section: Discussionmentioning
confidence: 99%
“…Like Arf6, overexpression of the AMAP1 protein in highly invasive breast cancer cells is also independent of the transcriptional upregulation of the AMAP1 gene (37). The 5’‐UTR of AMAP1 mRNA also possesses a very complicated secondary structure with a high free‐energy change ((40), Figure 2). We have observed that AMAP1 protein levels are downregulated in serum‐starved MDA‐MB‐231 cells, which is then upregulated swiftly upon EGF stimulation; and moreover, rapamycin reduces the AMAP1 protein levels in MDA‐MB‐231 cells (OBI, Osaka).…”
Section: Amap1 Is An Indicator Of the Malignant Potentials Of Breast mentioning
confidence: 99%
“…We have observed that AMAP1 protein levels are downregulated in serum‐starved MDA‐MB‐231 cells, which is then upregulated swiftly upon EGF stimulation; and moreover, rapamycin reduces the AMAP1 protein levels in MDA‐MB‐231 cells (OBI, Osaka). The 5’‐UTR of AMAP1 mRNA exhibits an internal ribosomal entry site (IRES) activity in differentiated monocytes (40). However, we have yet to study the precise mechanism involved in enhanced translation of the AMAP1 mRNA in malignant breast cancer cells (40).…”
Section: Amap1 Is An Indicator Of the Malignant Potentials Of Breast mentioning
confidence: 99%
See 1 more Smart Citation
“…While the expression of various genes has been correlated with the development of metastatic LSCC, and some of these have the potential to serve as markers of tumor progression in the clinic (30,31), the mechanistic details for LSCC remain to be determined. Previously, Miyata et al (32) identified a region in the 5'-UTR of AMAP1 that exhibits a significant internal ribosome entry site (IRES) activity in differentiated U937 cells. Moreover, this activity appears to be necessary for enhanced AMAP1 expression in this cell line.…”
Section: Discussionmentioning
confidence: 99%